Analisis Information and Communication Technology (ICT) Literacy Pengguna Aplikasi Sistem Informasi Manajemen Akademik (Studi Kasus: SIMAK Departemen SKPM) - Vidy Nalendra; Irman Hermadi; Ivanovich Agusta (Institut Pertanian Bogor, 2017)
Education management development, followed by the use of information technology are required by Department of Communication and Community Development Science, Faculty of Human Ecology, Bogor Agricultural University (SKPM FEMA IPB). System development is directed to the development of Academic Management Information System (MIS), which are interactive and provide information about academic. Department of Communication and Community Development Science developed an Academic Management Information System (Simak). Simak already developed but still have constraints in terms of users. User needs evaluation, ICT literacy measurement used as an approach to solving the constraints that exist for Simak users.